N-Substituted Prodrugs of Mebendazole Provide Improved Aqueous Solubility and Oral Bioavailability in Mice and Dogs - Zimmermann, Sarah C; Tichý, Tomáš; Vávra, Jan; Dash, Ranjeet P; Slusher, C Ethan; Gadiano, Alexandra J; Wu, Ying; Jančařík, Andrej; Tenora, Lukáš; Monincová, Lenka; Prchalová, Eva; Riggins, Gregory J; et al. (Journal of medicinal chemistry, 2018)
Mebendazole (MBZ) was developed as a broad-spectrum anthelmintic but has recently shown efficacy as an anticancer agent. The use of MBZ for cancer, however, is challenging due to its poor solubility leading to poor bioavailability. Herein, we developed a prodrug approach with various N-linked promoieties including acyloxymethyl, aminoacyloxymethyl, and substituted phosphonooxymethyl in attempt to improve these characteristics. Compound 12, containing an (((((isopropoxycarbonyl)oxy)methoxy)phosphoryl)oxy)methyl promoiety, showed a >10 000-fold improvement in aqueous solubility. When evaluated in mice, 12 displayed a 2.2-fold higher plasma AUC0- t and a 1.7-fold improvement in brain AUC0- t with a calculated oral bioavailability of 52%, as compared to 24% for MBZ-polymorph C (MBZ-C), the most bioavailable polymorph. In dogs, 12 showed a 3.8-fold higher plasma AUC0- t with oral bioavailability of 41% compared to 11% for MBZ-C. In summary, we have identified a prodrug of MBZ with better physicochemical properties and enhanced bioavailability in both mice and dog.
Keywords: stabilita léku; Animals; psi; Anthelmintics; Nitrogen; Prodrugs; Tissue Distribution; Biological Availability; mebendazol; Mebendazole; Structure-Activity Relationship; biologická dostupnost; Mice; Solubility; Drug Stability; rozpustnost; prekurzory léčiv; Dogs; myši; voda; Water; Male; aplikace orální; anthelmintika; tkáňová distribuce; vztahy mezi strukturou a aktivitou; Administration, Oral; zvířata; mužské pohlaví; dusík